2007
DOI: 10.1038/sj.bjc.6603972
|View full text |Cite
|
Sign up to set email alerts
|

Mucin impedes cytotoxic effect of 5-FU against growth of human pancreatic cancer cells: overcoming cellular barriers for therapeutic gain

Abstract: Mucins are high molecular weight glycoproteins expressed on the apical surface of normal epithelial cells. In cancer disease mucins are overexpressed on the entire cellular surface. Overexpression of MUC1 mucin in pancreatic tumours has been correlated with poor patient survival. Current chemotherapeutic approaches such as 5-fluorouracil (5-FU) has produced limited clinical success. In this study we investigated the role of mucin in cytotoxic drug treatment to determine whether the extracellular domain of muci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 32 publications
(29 reference statements)
2
35
0
Order By: Relevance
“…Our results show that MUC5B silencing in MCF-7 cells was associated with an increase sensitivity to 5-FU or cisplatin induced-death. In support of these findings, the ectopic overexpression of MUC4 or the knockdown of MUC1 and MUC4 on tumor cells was associated with a decreased sensitivity of these cells to various chemotherapeutic drugs (9,(36)(37)(38)(39)(40). Since mucins are high-molecular weight glycoproteins, they could restraint the drug accessibility to the tumor cell, limiting their effectiveness in inducing cell-killing (4).…”
Section: Discussionsupporting
confidence: 49%
“…Our results show that MUC5B silencing in MCF-7 cells was associated with an increase sensitivity to 5-FU or cisplatin induced-death. In support of these findings, the ectopic overexpression of MUC4 or the knockdown of MUC1 and MUC4 on tumor cells was associated with a decreased sensitivity of these cells to various chemotherapeutic drugs (9,(36)(37)(38)(39)(40). Since mucins are high-molecular weight glycoproteins, they could restraint the drug accessibility to the tumor cell, limiting their effectiveness in inducing cell-killing (4).…”
Section: Discussionsupporting
confidence: 49%
“…Interestingly, mucin MUC1 overexpression in some PDAC cell lines, including HPAF-II, has been shown to limit the uptake of anticancer drugs by tumor cells (64,65). It is possible that MUC1 and other mucins mask LDLR and prevent both VSV attachment and LDL uptake.…”
Section: Figmentioning
confidence: 99%
“…It is a highly aggressive cancer that is usually diagnosed at an advanced stage and has the worst prognosis of any malignancy, with a 7% 5-year survival rate due to high chemoresistance. This chemoresistance is due in part to altered expressions of mucins, which form a mesh that makes target sites inaccessible to drugs (2)(3)(4)(5)(6)(7)(8)(9). Clinical and preclinical studies have shown aberrant expression of mucins during pancreatic cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of several mucins, including MUC1, MUC4, MUC5AC, and MUC16, is highly upregulated in pancreatic ductal adenocarcinoma (PDAC), pancreatic intraepithelial neoplasia (PanIN), intrapapillary mucinous neoplasms, and mucinous cystic neoplasms from patients with pancreatic cancer (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The extent to which the dense mucin mesh influences the antiproliferative activity of 5-fluorouracil (5-FU) was investigated using human pancreatic cancer cells (2,3). These studies have led to increasing recognition of mucins as potential diagnostic markers and therapeutic targets in pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%